New criterion for in situ, quick discrimination between traditionally maintained and artificially restored Japanese swords (katanas) by XRF spectroscopy. (10th September 2013) - Castelli, L.; Giuntini, L.; Taccetti, F.; Barzagli, E.; Civita, F.; Czelusniak, C.; Fedi, M. E.; Gelli, N.; Grazzi, F.; Mazzinghi, A.; Palla, L.; Romano, F.P.; et al.
<x xml:space="preserve">Abstract</x> For the first time, a quick method to discriminate between undamaged, well‐maintained katanas and worn artificially restored blades is presented. The peculiar hardening process that a Japanese katana undergoes results in creation of a tempered martensitic phase near the blade edge. After the temper, traditional polishing with stones is performed, which gives the sword its final look: the hardened zone exhibits matte finish, and it is separated from the shinier zone by the hamon line, which is the most characteristic feature of a katana. If the sword is worn, the martensitic phase disappears and so does the hamon line, the sword losing most of its commercial value. However, an acid bath can simulate the matte texture of an undamaged martensitic structure, making it really difficult to recognize valuable blades from worn ones. So far, no analytical approach helping in this task was available. The method we present is based on the hypothesis that traditional polishing leaves a very tiny amount of stone dust on the blade, whereas the acid bath rinses it away. The presence on the blade surface of Si (the major component of the stones used for polishing) when the hamon line is clearly visible could thus be a reasonable marker indicating that the blade is maintaining its original martensitic structure and thus is in a good conservation state. For the Si detection, X‐ray fluorescence technique was chosen, which ensures non‐destructivity, high sensitivity, and short measurement time with a portable instrument. Copyright © 2013 John Wiley & Sons, Ltd.